PEMANFAATAN DATA TANAH DAN IKLIM UNTUK POLA TANAM PADI, UBI KAYU DAN JAGUNG DI KECAMATAN NGAWEN DAN GEDANGSARI, GUNUNGKIDUL - , AHMAD ALIMUDIN M. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study aims to determine the level of potential land in accordance with the conditions required by rice, cassava and maize in Ngawen and Gedangsari District, Gunungkidul and planting pattern in accordance whit the existing weather data. Determination of the level of land potential by applying a simple limitation method using rainfed rice growing conditions, cassava and maize according to Djaenudin et al., (2003). The result indicated that land suitability classes off rice is S3eh1 14,26 %, S3eh1eh2 15,88 %, Neh1 47,60% and Neh1eh2 0,86 %. Land suitability classes off cassava is S3eh1rc3 14,26 %, S3eh1eh1 15,88 %, Neh1 47,60% and Neh1eh2 0,86 land suitability classes off maize is S3eh1 14,26 %, S3eh1eh2 15,88 %, Neh1 47,60% and Neh1eh2 0,86 %. The main limiting factor is slope (eh1). Recommendation 1 of cropping pattern at Gedangsari for rice planted at first ten-days of November, cassava at third ten-days of September and maize at first tendays of March. Recommendation 2 of cropping pattern at Gedangsari for rice planted at first tendays of October and second ten-days of February, and cassava second ten-days of September. Recommendation 1 of cropping pattern at Ngawen for rice planted at first ten-days of October, cassava at first ten-days of September and maize at second ten-days of February. Recommendation 2 of cropping pattern at Ngawen for rice planted at first ten-days of October and second ten-days of February, and cassava first ten-days of September.